GLExee Integration with the ATLAS PanDA Workload Management System. Issue 6 (December 2015) - Karavakis, E; Barreiro, F; Campana, S; De, K; Girolamo, A Di; Litmaath, M; Maeno, T; Medrano, R; Nilsson, P; Wenaus, T
Abstract: ATLAS user jobs are executed on Worker Nodes (WNs) by pilots sent to sites by pilot factories. This paradigm serves to allow a high job reliability and although it has clear advantages, such as making the working environment homogeneous, the approach presents security and traceability challenges. To address these challenges, gLExec can be used to let the payloads for each user be executed under a different UNIX user id that uniquely identifies the ATLAS user. This paper describes the recent improvements and evolution of the security model within the ATLAS PanDA system, including improvements in the PanDA pilot, in the PanDA server and their integration with MyProxy, a credential caching system that entitles a person or a service to act in the name of the issuer of the credential. Finally, it presents results from ATLAS user jobs running with gLExec and describes the deployment campaign within ATLAS.